496 THE INFLAMMATORY-METAPLASIA-DYSPLASIA-OESOPHAGEAL ADENOCARCINOMA SEQUENCE: THE ROLE OF THE MICROBIOME. (14th September 2020) - Barrett, M; Elliott, J; Hand, C; Shanahan, F; O'Toole, P; Murphy, T
Abstract: : The human microbiota, the collection of microbes that inhabit the human body, is increasingly recognized as playing a role in human health. A seminal example of this relationship is Helicobacter pylori and gastric cancer oncogenesis. The decline in H.pylori prevalence and non-cardia gastric cancer incidence have coincided with the rise in oesophageal adenocarcinoma (OAC) incidence. We sought to explore the relationship between the gastric and oesophageal microbiome and OAC oncogenesis. Methods: This study aimed to explore changes in the microbiome associated with oesophageal adenocarcinoma and its precancerous and inflammatory states by performing 16S rRNA gene amplicon sequencing on DNA extracted from oesophago-gastric biopsies from patients with normal oesophageal mucosa, reflux oesophagitis, Barrett's oesophagus with and without dysplasia, locally advanced but resectable oesophageal adenocarcinoma, and incurable metatstatic oesophageal adenocarcinoma (See Table 1). We dissected ecological differences between sample site and clinical classification using a variety of approaches including examining differentially abundant taxa and inferred metabolic pathways, alpha diversity and beta-diversity. Results: There was no statistically significant difference in beta diversity with respect to biopsy location. Alpha diversity was reduced in gastric biopsies compare to oesophageal biopsies. A small but significant shift was noted in beta diversity (Bray–Curtis Dissimilarity) with respect to clinical classification in biopsies derived from the gastroesophageal junction (GEJ) and stomach. Fusobacterium nucleatum was found to overrepresented in oesophageal biopsies derived from diseased groups relative to the healthy controls. Several taxa assigned to the genus Prevotella were depleted in biopsies of individuals with metastatic OAC compared to all other groups. Conclusion: Community structure was shifted in samples derived from the GEJ, the epicentre of OAC oncogenesis. Fusobacterium plays a role in cancer development and progression through a number of mechanisms including increasing cell proliferation, immune cell infiltration and chemoresistance. Fusobacterium can cause upregulation of MicroRNA-21, a microRNA upregulated in OAC.